2011
DOI: 10.1007/s12402-011-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Training of attention functions in children with attention deficit hyperactivity disorder

Abstract: Pharmacological treatment of children with ADHD has been shown to be successful; however, medication may not normalize attention functions. The present study was based on a neuropsychological model of attention and assessed the effect of an attention training program on attentional functioning of children with ADHD. Thirty-two children with ADHD and 16 healthy children participated in the study. Children with ADHD were randomly assigned to one of the two conditions, i.e., an attention training program which tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 26 publications
2
37
1
12
Order By: Relevance
“…Thus, Karbach and Kray (2009) demonstrated both near transfer effects, with criterial tasks similar to training tasks, and far transfer effects, with criterial tasks not resembling the training tasks (see : Shipstead, Redrick, & Engle, 2010). Tucha et al (2011) also demonstrated effective training of attention. Thirty-six children diagnosed with ADHD and 16 healthy children (passive control group) participated in the study.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, Karbach and Kray (2009) demonstrated both near transfer effects, with criterial tasks similar to training tasks, and far transfer effects, with criterial tasks not resembling the training tasks (see : Shipstead, Redrick, & Engle, 2010). Tucha et al (2011) also demonstrated effective training of attention. Thirty-six children diagnosed with ADHD and 16 healthy children (passive control group) participated in the study.…”
mentioning
confidence: 93%
“…Such changes were not found in healthy control children or children who practiced perceptual tasks, indicating that the improvement did not stem from mere repetition of assessment with the same tasks. Tucha et al's (2011) study demonstrated both near and far transfer on previously untrained aspects of attention, but the author did not measure transfer to general intelligence. The current research therefore aimed at application of training tasks similar to those used in Tucha et al's (2011) study but also referring to all four aspects of attention highlighted by Coull (1998).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Methodologische tekortkomingen van studies bestaan verder uit onduidelijke randomisatieprocedures, het niet beoordelen van medicatietrouw en de afwezigheid van placebo-en controlegroepen van personen zonder ADHD. Eerder onderzoek naar de farmaceutische behandeling van ADHD heeft aangetoond dat deze behandeling kan resulteren in verbeteringen in het gedrag en de cognitie, maar dat het gedrag en het cognitief functioneren er niet per definitie mee normaliseren [86][87][88][89]. Literatuur gerelateerd zijn aan rij-gerelateerde problemen (bijv.…”
Section: Conclusieunclassified
“…As editors of the Attention-Deficit Hyperactivity Disorders, we are happy that some of these important areas of concern are addressed in the current issue. Tucha et al (2011) conducted an initial study assessing the impact of an attention training program based on a previous established neuropsychological model in improving attentional functioning of a small group of children with ADHD previously medicated. The intervention proposed was feasible to implement in clinical settings with adequate external validity (twice a week sessions per 4 weeks).…”
mentioning
confidence: 99%